An Example of the Use of Chemical Analyses in Evaluation of a Mineral Prospect (The Australasian Institute of Mining and Metallurgy, 1973)
A numerical method for discriminating between replacement and sedimentary processes is applied to a folded stratiform sulphide occurrence. It is shown that numerical treatment of chemical analyses from a single diamond drill hole allowed a rapid assignment of the ore to the syngenetic sedimentary class and thereby enabled a revision of the evaluation program concerned with consequent reduction in costs.